Different Changes of Risks for Stroke and Myocardial Infarction in Patients With Type 2 Diabetes in Hungary Between the Two Periods of 2001–2004 and 2010–2013 - Kiss, Zoltan; Rokszin, György; Abonyi-Tóth, Zsolt; Jermendy, György; Kempler, Péter; Wittmann, István (Frontiers in Endocrinology, 2019)
Objective In recent decades several studies reported significant changes in the mortality and morbidity of patients with type 2 diabetes. In this Hungarian nationwide study, we assessed the changes of mortality and cardiovascular risks comparing a group of patient diagnosed during the two periods of 2001-2004 and 2010-2013. Research Design and Methods We identified patients with type 2 diabetes recorded in the database of the Hungarian National Health Insurance Fund aiming to assess changes of risks for all-cause mortality, myocardial infarction and stroke during the follow-up periods of 48 months. Results We included 274,109 patients with newly diagnosed type 2 diabetes between 2001 and 2004, while only 152,678 in the 2010-2013 period. The risk of all-cause mortality at the beginning of the follow-up was not different comparing 2010-2013 to 2001-2004 (HR 1.03), and a mild but significant decrease could be detected (HR 0.87) after 48 months. A lower risk for myocardial infarction was documented in the second month after the diagnosis of diabetes (HR 0.67), which remained constant during the study period and almost the same after 48 months (HR 0.73). On the contrary, our study verified a slightly increased risk for stroke close to the diagnosis (HR 1.06 (1.00-1.13)) and a decreased one (HR 0.72 (0.69-0.79)) at the end of the study. Conclusions An increased risk for stroke followed by a sharp decrease, and an unchanged risk for myocardial infarction in the Hungarian population with type 2 diabetes possibly resulted in a mild decrease of all-cause mortality between 2001 and 2013.